Horn Antenna on Chip Operating at 180 GHz Using the SiGe CMOS Process - Ming-An Chung; Zi-Yu Huang; Yu-Hsun Chen (Telecom, 2024)
This article proposes a chip antenna on millimeter-Waves. This antenna combined with TSMC 180 nm SiGe CMOS technology has the advantage of being small in size and is suitable for wireless communications. The multilayer architecture Horn antenna implemented on M4–M6 can meet both process reliability specifications and radiation performance. The results of the simulation show that the maximum gain is −4.2 dBi. The return loss measurement results are almost consistent with the simulation results, and the bandwidth range is 177.4–183 GHz. This article first describes the antenna production process and measurement results, analyses the impact of the parameters on the antenna, and further compares it with other designs. The excellence of this article is that it proposes a design that solves the problem of large millimeter wave loss and successfully reduces the area. At the same time, this article can contribute to readers’ future optimization and continued research directions, and at the same time contribute simulation and measurement trends to let readers understand the stability of CMOS chip antenna simulation and measurement.